TINJAUAN UNDANG-UNDANG DALAM PERCERAIAN DI LUAR PENGADILAN AGAMA - Fajri, Muhamad; Silahuddin, Muhammad (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
This study aims to explain the phenomenon of divorce outside the court according to Law Number 1 of 1974 concerning Marriage. In the context of positive law in Indonesia, the divorce procedure is regulated in a registered process. To avoid negative impacts, the Indonesian government issued a regulation that divorce can only be carried out in front of a court session. This research uses a qualitative phenomenological type of research with a case study approach and library research by conducting an assessment of the laws and regulations, books, and fiqh books related to the title of this thesis. The primary data in this study is qualitative data obtained through interviews and observations. The findings of the study indicate that the factors causing divorce outside the religious court in Rancagong Village, Legok District, are habits that often consider complicated procedures and stages in the divorce process at the Religious Courts, the unaffordable cost of the religious court process, the assumption that only the word divorce is legally binding. there is a direct legality of divorce according to religion (customary law), and the lack of information on the importance of a law in population status in Indonesia